Customer Satisfaction & Loyalty in the Singapore Retail Fuel Market - Koh, See Yong (2009)
Where are all the customers? If your competitors have got them, then it’s a bad news. The good news is that you can win them back or attract new ones. This may sound simple and easy. However, the starkest challenge facing business today is customer scarcity where they are too many sellers for too few buyers.